Effects of plasma on polyethylene ﬁber surface for prosthodontic application - Silvana Marques Miranda SPYRIDES; Maíra do PRADO; Joyce Rodrigues de ARAUJO; Renata Antoun SIMÃO; Fernando Luis BASTIAN (University of São Paulo, 2015)
ABSTRACT Plasma technology has the potential to improve the adherence of fibers to polymeric matrices, and there are prospects for its application in dentistry to reinforce the dental particulate composite. Objectives This study aimed to investigate the effect of oxygen or argon plasma treatment on polyethylene ﬁbers. Material and Methods Connect, Construct, InFibra, and InFibra treated with oxygen or argon plasma were topographically evaluated by scanning electron microscopy (SEM), and chemically by X-ray photoelectron spectroscopy (XPS). For bending analysis, one indirect composite (Signum) was reinforced with polyethylene fiber (Connect, Construct, or InFibra). The InFibra fiber was subjected to three different treatments: (1) single application of silane, (2) oxygen or argon plasma for 1 or 3 min, (3) oxygen or argon plasma and subsequent application of silane. The samples (25x2x2 mm), 6 unreinforced and 60 reinforced with fibers, were subjected to three-point loading tests to obtain their flexural strength and deflection. The results were statistically analyzed with ANOVA and the Bonferroni correction for multiple comparison tests. Results SEM analysis showed that oxygen and argon plasma treatments promote roughness on the polyethylene fiber surface. X-ray photoelectron spectroscopy (XPS) analysis shows that both plasmas were effective in incorporating oxygenated functional groups. Argon or oxygen plasma treatment affected the flexural strength and deflection of a fiber reinforced composite. The application of silane does not promote an increase in the flexural strength of the reinforced composites. Conclusions Oxygen and argon plasma treatments were effective in incorporating oxygenated functional groups and surface roughness. The highest strength values were obtained in the group reinforced with polyethylene fibers treated with oxygen plasma for 3 min.